Effects of Crude Extract of Ageratum Conyzoides, Moringa Oleifera and Zanthoxylum Zanthoxyloides on Serum Lipid Profile in Albino Rats - O.I, OYEWOLE; A.G, ADEBAYO; S.M, OGUNSAKIN (The International Journal of Biotechnology, 2012)
Ageratum conyzoides, Moringa oleifera and Zanthoxylum zanthoxyloides are among medicinal plants commonly used in African folk medicine as remedies for the treatments of high blood pressure and heart related diseases. This study was carried out to compare the effects of Ageratum conyzoides, Moringa oleifera and Zanthoxylum zanthoxyloides extracts on serum lipid profile in albino rats. Thirty five albino rats were grouped into seven each containing five rats. Control rats (Group 1) received distilled water while test groups (2-7) were administered the extracts at two dose levels (200mg/kg bw and 500mg/kg bw) for 14 days. Results indicated that Moringa oleifera and Zanthoxylum zanthoxyloides extracts caused significant reduction in the concentrations of serum total cholesterol, triacylglycerol and LDL-cholesterol with Moringa oleifera having the most significant effect. There was also a significant increase in HDL-cholesterol concentration in rats administered Zanthoxylum zanthoxyloides compared with the control. Treatment of rats with Ageratum conyzoides had no effects on lipid metabolism as there was no significant changes in lipid profile of rats treated with this extract compared with the control. This result implies that Moringa oleifera and Zanthoxylum zanthoxyloides might be useful in the treatment of hypertension and other cardiovascular diseases arising from hyperlipidemia.